Taking a Holistic Approach to Planning and Developing Hydropower : Lessons from Two River Basin Case Studies in India - Haney, Michael; Plummer, Judith (World Bank, Washington, DC, 2012)
Planning for hydropower development needs to evolve from a project-based engineering approach to a more holistic one - an approach incorporating river basin planning and integrating potential social and environmental issues across multiple projects and the entire river basin. Such a framework would help to optimize the benefits and minimize the costs. It would also bring stakeholders together to weigh opportunities and risks and form a consensus for sustainable and equitable development. A Public-Private Infrastructure Advisory Facility (PPIAF)-funded study on two river basins in India's Himalayan region outlines steps for moving toward such a holistic framework.